DESAFÍOS ÉTICOS Y LEGALES PARA LOS FOTOGRAFOS EN LA ERA DIGITAL - AVILEZ GARCÍA, KIMBERLY JANETH (2024)
SUMMARY This research is based on the ethical and legal challenges that photographers face in the digital era in the city of Babahoyo. This study analyzes the complexities that exist in taking photographs online. Through descriptive and inductive research, data obtained from interview and documentary review techniques will be studied, with the sole objective of arguing about the perceptions of both photography professionals and regulatory documents that are directly linked to this discipline. This study seeks to contribute to knowledge and align with the photographic regulations of the current era, as well as strengthen ethical practices in the workplace of photography. By examining these factors, we seek to promote the professional development of photographers in a comprehensive manner and promote responsible practice. The study of the ethical and legal challenges for photographers in the digital era in Babahoyo has the possibility of serving as a foundation for future generations of young professionals who aspire to work in this field.